Lactate transport and receptor actions in cerebral malaria - Mariga, Shelton T.; Kolko, Miriam; Gjedde, Albert; Bergersen, Linda H. (Frontiers in Neuroscience, 2014)
Cerebral malaria (CM), caused by Plasmodium falciparum infection, is a prevalent neurological disorder in the tropics. Most of the patients are children, typically with intractable seizures and high mortality. Current treatment is unsatisfactory. Understanding the pathogenesis of CM is required in order to identify therapeutic targets. Here, we argue that cerebral energy metabolic defects are probable etiological factors in CM pathogenesis, because malaria parasites consume large amounts of glucose metabolised mostly to lactate. Monocarboxylate transporters (MCTs) mediate facilitated transfer, which serves to equalize lactate concentrations across cell membranes in the direction of the concentration gradient. The equalizing action of MCTs is the basis for lactate’s role as a volume transmitter of metabolic signals in the brain. Lactate binds to the lactate receptor GPR81, recently discovered on brain cells and cerebral blood vessels, causing inhibition of adenylyl cyclase. High levels of lactate delivered by the parasite at the vascular endothelium may damage the blood-brain barrier, disrupt lactate homeostasis in the brain, and imply MCTs and the lactate receptor as novel therapeutic targets in CM.